2012
DOI: 10.1007/s13762-012-0117-8
|View full text |Cite
|
Sign up to set email alerts
|

Control of the biofouling bryozoan, Plumatella repens, using pulsed chlorine treatment

Abstract: Bryozoans are common biofoulers of underdrain filter nozzles in rapid gravity filters in water treatment works. A potential method for controlling bryozoan biofouling is the use of chlorine in backwash water. Repeatedly exposing bryozoan colonies with chlorine for 20 min every 24 h in an experimental setting, to replicate what would occur if the backwash was chlorinated, caused significant reduction in colony growth and size. After 10 days repeated treatment in good conditions for bryozoan propagation, the EC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Plumatellid bryozoans are frequently recorded in waterbird excreta (Brochet, Gauthier‐Clerc, et al., ; Green et al., ), but to our knowledge, this is the first confirmation that birds are vectors for alien bryozoans such as P. vaihiriae , although this is considered likely for other aliens such as Pectinatella magnifica (Balounová, Pechoušková, Rajchard, Joza, & Šinko, ). The ability of bryozoans to disperse by birds may increase the economic costs they impose through biofouling of pipes and pumps (Mant, Moggridge, & Aldridge, ). It is likely that the Plumatella statoblasts we recorded became stuck onto P. clarkii via mud.…”
Section: Discussionmentioning
confidence: 99%
“…Plumatellid bryozoans are frequently recorded in waterbird excreta (Brochet, Gauthier‐Clerc, et al., ; Green et al., ), but to our knowledge, this is the first confirmation that birds are vectors for alien bryozoans such as P. vaihiriae , although this is considered likely for other aliens such as Pectinatella magnifica (Balounová, Pechoušková, Rajchard, Joza, & Šinko, ). The ability of bryozoans to disperse by birds may increase the economic costs they impose through biofouling of pipes and pumps (Mant, Moggridge, & Aldridge, ). It is likely that the Plumatella statoblasts we recorded became stuck onto P. clarkii via mud.…”
Section: Discussionmentioning
confidence: 99%
“…In a full-scale RO plant, Hoek and co-workers renewed the methodology of disinfection followed by chlorination, microfiltration, and dechlorination along with ultraviolet (UV) irradiation, chlorine dioxide (ClO 2 ), and granular activated carbon (GAC) to prevent befouling on the downstream process in RO membrane (Fujiwara and Matsuyama 2008). The pre-treatment with ultraviolet was not effective, whereas ClO 2 and GAC performed satisfactorily, even though ClO 2 destroys certain membranes (Mant et al 2013;Ghosh et al 2019). 2,2-Dibromo-3-nitrilopropioamide (DBNPA), non-oxidative biocide, can similarly be used to inhibit or eradicate the difficulties owing to the accumulation of biofouling and confirm the long-term performance of the RO system (Bertheas et al 2009).…”
Section: Trends For Prevention and Control Of Membrane Biofoulingmentioning
confidence: 99%
“…The authors concluded that improvements of anti-fouling methods would substantially reduce the annual budget spent on biofouling and the savings would eventually cover the cost of research and implementation of new techniques. Similarly, the UK water industry spent £1.49M over a four-year period due to persistent foulers; with common, biofouling bryozoans being discovered growing on rapid gravity filters within these facilities reducing the effectiveness of the filter (Mant et al, 2011;Mant et al, 2013).…”
Section: Introductionmentioning
confidence: 99%